2020
DOI: 10.1177/1477153520902255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-wavelength light on electroencephalogram and subjective alertness

Abstract: This study extends previous findings on the effect of different levels of short-wavelength light on human alertness. This study explores the alerting ability of long-wavelength light at two levels (40 lx and 160 lx). Eight subjects took part in the 60-minute experiment for each of two nights, during which their objective alertness and subjective alertness were evaluated using electroencephalogram and questionnaire. Results show that both levels increased electroencephalogram beta power, which shows a different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…As circadian photoreceptors, ipRGCs, are most sensitive to blue (short wavelength) light, CS failed to explain the impact of red (long wavelength) light on the circadian system. Red light was found to affect the circadian system by increasing alertness without suppressing melatonin [117][118][119][120]. In addition, the CS metric considers melatonin suppression and phase-shifting as proxies.…”
Section: Circadian Stimulus Metricmentioning
confidence: 99%
“…As circadian photoreceptors, ipRGCs, are most sensitive to blue (short wavelength) light, CS failed to explain the impact of red (long wavelength) light on the circadian system. Red light was found to affect the circadian system by increasing alertness without suppressing melatonin [117][118][119][120]. In addition, the CS metric considers melatonin suppression and phase-shifting as proxies.…”
Section: Circadian Stimulus Metricmentioning
confidence: 99%
“…The subjects did not look directly at the light source to avoid the possible afterimage effect and enhance the immersive atmosphere. 11…”
Section: Experiments Setupmentioning
confidence: 99%
“…6,7 The difference of illuminance, wavelength, and correlated color temperature (CCT) of colors directly affects personal behavior and psychology and physiology. [8][9][10][11] For most situations, a specific physical stimulus can only produce a single perceptual experience. But for synaesthesia, one physical stimulus can induce more than one sensation.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the effective use of colours in the design of classrooms do have significant impacts on students’ perceptual performances. Interestingly, some studies carried out explored the intensity lighting impacts have on people’s electroencephalogram (EEG) power [ 15 , 16 ]. Results have demonstrated the stimulus of short and long wavelength light on people’s alpha, theta, and beta power, suggesting that coloured light can promote acute alertness and improve performance on tasks requiring sustained attention.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the effective use of colours in the design of classrooms do have significant impacts on students' perceptual performances. Interestingly, some studies carried out explored the intensity lighting impacts have on people's electroencephalogram (EEG) power [15,16].…”
Section: Introductionmentioning
confidence: 99%